Ibritumomab Tiuxetan Radioimmunotherapy for Primary Gastrointestinal Follicular Lymphoma. (21st July 2021) - Desai, Sanjal; Moustafa, Muhamad Alhaj; Wiseman, Gregory; Witzig, Thomas
Abstract : Primary gastrointestinal follicular lymphoma (PGIFL) is characterized by localized involvement of the gastrointestinal (GI) tract. PGIFL usually runs an indolent course. External beam radiation therapy is curative in a substantial proportion of localized follicular lymphomas, but GI toxicities may discourage its use in PGIFL. Ibritumomab tiuxetan radioimmunotherapy (RIT) is a radioimmunoconjugate of anti-CD20 monoclonal antibody linked to chelator tiuxetan and radioisotope. RIT delivers confined high-intensity radiation with short path length specifically targeting lymphoma cells and sparing normal tissue. In this case series report, we included six cases of PGIFL treated with RIT. All patients had low-risk, localized, and nonbulky disease. All patients responded completely and were relapse-free for the duration of follow-up. Hematologic toxicities were seen, but none were serious. RIT is a potentially curative treatment option in PGIFL with a tolerable toxicity profile. Abstract : This case series reports six cases of primary gastrointestinal follicular lymphoma treated with ibritumomab tiuxetan radioimmunotherapy, with good results.